24-h activity rhythm and sleep in depressed outpatients. (June 2016) - Hori, Hiroaki; Koga, Norie; Hidese, Shinsuke; Nagashima, Anna; Kim, Yoshiharu; Higuchi, Teruhiko; Kunugi, Hiroshi
Abstract: Disturbances in sleep and circadian rest-activity rhythms are key features of depression. Actigraphy, a non-invasive method for monitoring motor activity, can be used to objectively assess circadian rest-activity rhythms and sleep patterns. While recent studies have measured sleep and daytime activity of depressed patients using wrist-worn actigraphy, the actigraphic 24-h rest-activity rhythm in depression has not been well documented. We aimed to examine actigraphically measured sleep and circadian rest-activity rhythms in depressed outpatients. Twenty patients with DSM-IV major depressive episode and 20 age- and sex-matched healthy controls participated in this study. Participants completed 7 consecutive days of all-day actigraphic activity monitoring while engaging in usual activities. For sleep parameters, total sleep time, wake after sleep onset, and sleep fragmentation index were determined. Circadian rhythms were estimated by fitting individual actigraphy data to a cosine curve of a 24-h activity rhythm using the cosinor method, which generated three circadian activity rhythm parameters, i.e., MESOR (rhythm-adjusted mean), amplitude, and acrophase. Subjective sleep was also assessed using a sleep diary and the Pittsburgh Sleep Quality Index. Patients showed significantly lower MESOR and more dampened amplitude along with significant sleep disturbances. Logistic regression analysis revealed that lower MESOR and more fragmented sleep emerged as the significant predictors of depression. Correlations between subjectively and actigraphically measured parameters demonstrated the validity of actigraphic measurements. These results indicate marked disturbances in sleep and circadian rest-activity rhythms of depression. By simultaneously measuring sleep and rest-activity rhythm parameters, actigraphy might serve as an objective diagnostic aid for depression.